Beneficial effects of balloon pulmonary angioplasty on clinical outcomes in patients with residual pulmonary hypertension after pulmonary endarterectomy. (25th November 2020) - Iwanaga, T; Aoki, T; Ogo, T; Tsuji, A; Ueda, J; Hirakawa, K; Nakayama, S; Asano, R; Inoue, Y; Uehara, K; Sasaki, H; Matsuda, H; et al.
Abstract: Background: Although pulmonary endarterectomy (PEA) is an established surgical treatment for chronic thromboembolic pulmonary hypertension (CTEPH), a part of patients after PEA show residual pulmonary hypertension, leading to limited exercise capacity. Recently, several studies have indicated that balloon pulmonary angioplasty (BPA) improves hemodynamics, exercise capacity and prognosis in inoperable CTEPH patients. However, the effects of BPA in patients with residual pulmonary hypertension after PEA remain to be elucidated. Aim: In the present study, we investigated comprehensive efficacy of BPA on hemodynamics, exercise capacity and right ventricular function in those with residual pulmonary hypertension after PEA. Methods: From October 2010 to February 2019, 227 patients with CTEPH underwent PEA in our institution. Right heart catheterization after PEA (median follow up period from PEA to right heart catheterization 39 [10.5, 90] months) showed that 55 patients showed residual PH (mean pulmonary artery pressure (mPAP)≥25mmHg), and 38 of them referred to BPA (mean age 57 years old, male 8 (21%)) due to residual symptoms. In 29 out of 38 patients (76%) who completed BPA and underwent follow-up right heart catheterization, we examined hemodynamics, exercise capacity and right ventricular function before and after BPA. Follow-up examination was performed 3 months after last BPA session. Results: In this study population (N=29), PEA significantly improved mPAP (47±7 to 38±10 mmHg), pulmonary vascular resistance (PVR, 14.6±4.6 to 9.2±4.6 WU) and right ventricular ejection fraction measured by magnetic resonance imaging (26.6±11.3 to 38.4±6.8%) (Figure). Median period from PEA to first BPA procedure was 42 [13.5, 94] months. Total session number during study period was 160 sessions, and mean session number of BPA was 5.5±1.5 per patient. Follow-up study revealed that BPA additionally improved mPAP (38±10 to 27±8 mmHg) and PVR (9.2±4.6 to 5.1±2.2 WU) (Figure). Similarly, 6-minute walk distance (393±125 to 452±125 m) and peak VO2 (16.4±3.8 to 18.1±4.6 ml/min/kg, p<0.05) were increased, and WHO functional class also significantly improved by BPA (I/II/III/IV, 0/21/8/ 0 to 1/27/1/0, p<0.01). In addition, right ventricular ejection fraction (38.4±6.8 to 44.2±7.1%) was increased after BPA (Figure). There were no procedure-related deaths and major lung injuries requiring oral intubation during study period. 3-year survival in patients after BPA was 100% (median follow-up period after last BPA session, 32 [18, 46] months). Conclusion: In CTEPH patients with residual pulmonary hypertension after PEA, additional BPA significantly improved hemodynamics, right ventricular function, exercise capacity and residual symptoms without severe complications, leading to good prognosis. These results suggest that combination therapy of PEA and BPA could be an effective therapeutic option for post PEA patients with residual symptoms and exercise limitation. Funding Acknowledgement: Type of funding source: None